2021
DOI: 10.1002/rcm.9159
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic dependence of Nile crocodile (Crocodylus niloticus) isotope diet‐to‐tissue discrimination factors

Abstract: Rationale The diet of wild Nile crocodiles (Crocodylus niloticus) is difficult to assess because they are cryptic and nocturnal predators that are extremely sensitive to disturbance by observers, and stomach content analysis is challenging, especially in large specimens. Stable light isotope analysis provides a means of assessing their diet, but diet‐to‐tissue discrimination factors have yet to be established for the species. Methods Isotope ratio (15N/14N and 13C/12C expressed as δ15N and δ13C) analyses of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Therefore, our SIA results present a broad picture of the isotopic landscape of the estuarine crocodile population over two different periods. We found that individuals became more 13 C-and 15 N-enriched as they grew, and this relationship was similar between 'historical' and 'contemporary' cohorts (figure 1 [27, [36][37][38][39] and other large carnivores that show indeterminate growth [40] and are suggested to reflect changes in diet and metabolism as the animal grows [38,41]. This evidence suggests that the δ 15 N of estuarine crocodiles scaled similarly with body size class under high (contemporary) and low (historic) population densities.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Therefore, our SIA results present a broad picture of the isotopic landscape of the estuarine crocodile population over two different periods. We found that individuals became more 13 C-and 15 N-enriched as they grew, and this relationship was similar between 'historical' and 'contemporary' cohorts (figure 1 [27, [36][37][38][39] and other large carnivores that show indeterminate growth [40] and are suggested to reflect changes in diet and metabolism as the animal grows [38,41]. This evidence suggests that the δ 15 N of estuarine crocodiles scaled similarly with body size class under high (contemporary) and low (historic) population densities.…”
Section: Resultsmentioning
confidence: 52%
“…We found that individuals became more 13 C- and 15 N-enriched as they grew, and this relationship was similar between ‘historical’ and ‘contemporary’ cohorts (figure 1 and table 1). Ontogenetic changes in isotopic values are common in crocodylians [27,3639] and other large carnivores that show indeterminate growth [40] and are suggested to reflect changes in diet and metabolism as the animal grows [38,41]. This evidence suggests that the δ 15 N of estuarine crocodiles scaled similarly with body size class under high (contemporary) and low (historic) population densities.…”
Section: Resultsmentioning
confidence: 98%
“…Ours is one of a few studies of isotopes from crocodilians to report isotope signatures from both collagen and keratin (Adame et al, 2018; Woodborne et al, 2021). Although caudal scutes are commonly used for isotopic analyses of crocodilians, scutes have rarely been separated into keratin and collagen fractions (Wheatley et al, 2011; Radloff et al, 2012; Caut, 2013; Smolensky et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that keratin has a faster turnover rate than collagen and therefore should reflect material assimilated over the previous few months, whereas collagen could reflect the diet over as much as a year (Spearman, 1966; Radloff et al, 2012; Rosenblatt and Heithaus, 2013). Indeed, Woodborne et al (2021) analyzed collagen and keratin in detail in Crocodilus niloticus and concluded that diet-to-tissue determinations were dependent on the type of tissue analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The methods described in Woodborne et al (2012) for time series dietary reconstruction from crocodilian claws could be applied on living animals to infer trophic dynamics of the aquatic/terrestrial interface at a decadal scale (Santos et al, 2018; Woodborne et al, 2021). This has larger implications for managing the Nile crocodile population of the Olifants River Gorge in the Kruger National Park.…”
Section: Discussionmentioning
confidence: 99%